The influence of Ca–Mg disorder on the growth of dolomite: a computational study. Issue 29 (6th July 2020) - Bruno, M.; Ghignone, S.; Pastero, L.; Aquilano, D.
Abstract : A new growth model for primary dolomite is proposed, in which a disordered dolomite/calcite interface seems to promote dolomite nucleation on a newly formed calcite crystal. Abstract : We performed empirical calculations at 0 K on the (10.4) slabs of dolomite with increasing thickness and different Ca 2+ –Mg 2+ distributions ( i.e., different degrees of structural disorder) in the 10.4 layers forming the slab. The energy of the isolated (10.4) dolomite slabs and (10.4) dolomite slabs in epitaxy with the (10.4) calcite slabs was determined. In particular, the (i) average potential energy, (ii) specific adhesion energy and (iii) excess free energy due to the presence of the interfaces were calculated for all the systems investigated. These data allowed us to propose a new growth model for primary dolomite, which hypothesizes that dolomite forms from a Ca 2+ –Mg 2+ -rich fluid by initially nucleating small calcite crystals, which act as substrates for successive dolomite formation. Moreover, our calculations suggest that the dolomite layers forming at the dolomite/calcite and dolomite/solution interfaces are disordered with increasing adhesion energy and decreasing surface energy. Then, a disordered dolomite/calcite interface seems to promote dolomite growth.